1996
DOI: 10.1080/10408399609527760
|View full text |Cite
|
Sign up to set email alerts
|

Allergenic foods

Abstract: Carrageenans are sulfated linear polysaccharides of D-galactose and 3,6-anhydro-D-galactose extracted from red seaweeds. They have been used by the food industry for their gelling, thickening, and stabilizing properties, and more recently by the meat industry for reduced fat products. Meat is a complex system of muscle tissue, connective tissue, fat, and water; during processing, numerous interactions occur among all these components. These interactions are responsible for the functional properties of the meat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
94
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(100 citation statements)
references
References 172 publications
1
94
0
4
Order By: Relevance
“…There has been an increase in the observed incidence of peanut allergies in children over the last 10 years. This is thought to be due to the increased popularity and use of peanut products by the population in the last decade and the introduction of peanut products to children's diets at an early age (2)(3)(4)(5). Thus, it is increasingly common for the public to be exposed to an abundantly utilized and often disguised food such as peanuts.…”
mentioning
confidence: 99%
“…There has been an increase in the observed incidence of peanut allergies in children over the last 10 years. This is thought to be due to the increased popularity and use of peanut products by the population in the last decade and the introduction of peanut products to children's diets at an early age (2)(3)(4)(5). Thus, it is increasingly common for the public to be exposed to an abundantly utilized and often disguised food such as peanuts.…”
mentioning
confidence: 99%
“…4,5) In 1999, the Joint FAO/WHO Codex Alimentary Commission agreed to label eight kinds of food which contain ingredients known to be allergens, including soybeans. 6,7) In Japan, the Ministry of Health, Labor and Welfare has enforced a labeling system for allergenic food material since April 2002.…”
mentioning
confidence: 99%
“…In children, the most common foods able to trigger an immunological response include, but are not limited to, cow's milk, hen's egg, peanut, soybeans, wheat, fish, and tree nuts. Whereas, in adults, the most common food allergies are due to ingestion of peanuts, tree nuts, fish, and shellfish [99][100][101]. In people, most commonly food allergy started in the first 3 years of life; however, several studies have shown that most allergies that begin early in life (e.g., milk, egg, soy, and wheat) are generally outgrown.…”
Section: Food Allergymentioning
confidence: 98%